Factors Behind Graduates Students’ Difficulties in Abstract Algebra: Evidence From University Students - Gnawali, Yagya Prasad; Acharya, Umesh (Ganeshman Darpan, 2026)
The main aims of this study are to identify the noteworthy factors that contribute to graduate students’ difficulties in learning abstract algebra. It pays a qualitative method using an ethnographic research design. The participants included five graduate students from the Department of Mathematics Education at Mahendra Ratna Campus, Tribhuvan University, who were completed the first semester of the master’s degree examination. The required data were collected through in-depth interviews and focus group discussions among the participants. We found from the interview data, on the basis of analysis four major factors which were main causes of students’ learning difficulties in abstract algebra. These were, prior knowledge, and lecturer performance, along with teaching methods and the nature of assignments and assessments. Previous understanding was found to be decisive for supporting student interest and participation, whereas current knowledge assisted as a substance for grasping new abstract ideas. Furthermore, the effectiveness of instructional strategies, the role of the teachers, and the value of assignments and assessments played a noteworthy role in shaping students’ comprehension and academic success in abstract algebra of graduate level.